(x^3-x^2-7x+3):(x-3)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x+1\right)^2+\left(3x-1\right)^2+2\left(2x+1\right)\left(3x-1\right)\)
\(=\left(2x+1\right)^2+2\left(2x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)
\(=\left[\left(2x+1\right)+\left(3x-1\right)\right]^2=\left(2x+3x+1-1\right)^2=25x^2\)
\(\left(2x+1\right)^2+\left(3x-1\right)^2+2\left(2x+1\right)\)\(\left(3x-1\right)\)
\(=\left(2x+1\right)^2+2\times\left(2x+1\right)\left(3x-1\right)\)\(+\left(3x-1\right)^2\)
\(=\left[\left(2x+1\right)+\left(3x-1\right)\right]^2\)
\(=\left(2x+1+3x-1\right)^2\)
\(=\left(5x\right)^2\)
\(=25x^2\)
Học tốt ~!
\(\left(x+y\right)^2+\left(x-y\right)^2-2\left(x+y\right)\left(x-y\right)\)
\(=\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)+\left(x-y\right)^2\)
\(=\left[\left(x+y\right)-\left(x-y\right)\right]^2=\left(x+y-x+y\right)^2=4y^2\)
a, \(A=\left(\frac{2}{x-2}-\frac{2}{x+2}\right)\frac{x^2+4x+4}{8}\)ĐK : \(x\ne\pm2\)
\(=\left(\frac{2\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}-\frac{2\left(x-2\right)}{\left(x+2\right)\left(x-2\right)}\right)\frac{\left(x+2\right)^2}{8}\)
\(=\frac{2x+2-2x+2}{\left(x-2\right)\left(x+2\right)}.\frac{\left(x+2\right)^2}{8}=\frac{4}{\left(x-2\right)\left(x+2\right)}.\frac{\left(x+2\right)^2}{8}\)
\(=\frac{x+2}{2\left(x-2\right)}=\frac{x+2}{2x-4}\)
b, A = x hay
\(\frac{x+2}{2x-4}=x\Leftrightarrow x+2=2x^2-4x\)
\(\Leftrightarrow5x+2-2x^2=0\)vô nghiệm
tương tự với A = x/2 nhé !
x^3 - x^2 - 7x + 3 x - 3 x^2 + 2x - 1 x^3 - 3x^2 2x^2 - 7x + 3 2x^2 - 6x -x + 3 -x + 3 0
Vậy \(\left(x^3-x^2-7x+3\right):\left(x-3\right)=x^2+2x-1\)